Percepções de professores de ciências da natureza da educação básica sobre a pesquisa em sala de aula presentes em narrativas - Silva, Carla Melo da (2017)
The objective of this dissertation is to analyze narratives of teachers of Natural Sciences, of Basic Education, about research in the classroom. For this, was analyzed the narratives of 27 teachers, who were enrolled in a postgraduate program in Education in Science and Mathematics of a Communitary University from the South of Brazil. These participants narrated situations in which they experienced the research in the classroom, as a teacher or as a student. For analysis, the narratives were transformed in monads, following propose by Walter Benjamin. For the monads composition, it was used Labov’s Logic to avoid narratives variability. The monads with similar contents were gathered, constituting the amalgams of monads. In these groups, the teachers' perceptions about the research in the classroom were identified, based on the following investigation question.: How the perceptions of Nature Science teachers’ of the Basic Education about research in classroom are presents in your narratives? Research has shown that participants consider relevant classroom research. They affirm that it is a way of enhancing relations between the subjects of learning and of making autonomy and critical formation possible. They point to several positive factors when compared to traditional teaching practices. However, they say that it is a little used practice in classrooms. They mention that teacher education does not qualify for the use of classroom research in schools. Therefore, research as a pedagogical principle and as a method of teaching and learning needs to be studied in theory and practice in teacher training courses. This may allow the teacher in training to see himself as a researcher and recognize the relevance of research to learning.